EFEKTIVITAS PEMBELAJARAN ANAK BERKEBUTUHAN KHUSUS PADA GURU PENDIDIKAN ANAK USIA DINI - Palintan, Tien Asmara; Ashari, Novita; Rauf, Abdul (Institut Agama Islam Negeri (IAIN) Manado, 2023)
ABSTRACTEarly childhood teachers are expected to be able to handle and provide services for children with special needs. In fact, early childhood teachers experience difficulties in educating children with special needs due to limited understanding and experience in directly educating children with special needs. The purpose of this study was to determine whether there are differences in early childhood teachers' skills before and after training in teaching children with special needs. The participants in this study were teachers from Parepare city. The number of participants involved in this study was 35 preschool teachers. This research is a pre-experimental design with a one-group pretest-posttest design. This research instrument uses a test instrument and a teacher response questionnaire. Research data were obtained through the administration of tests given before and after the implementation of treatment. The results of this study showed that early childhood teachers' skills in teaching children with disabilities improved significantly. This shows that the training has a positive impact on improving early childhood teachers' skills. Keywords: Early Childhood Teachers, Special Needs Children Education ABSTRAKGuru PAUD diharapkan mampu melakukan penanganan dan pemberian layanan terhadap anak berkebutuhan khusus (ABK). Namun faktanya, guru PAUD mengalami kesulitan dalam mendidik ABK usia dini dengan alasan pemahaman dan pengalaman yang terbatas dalam mendidik ABK secara langsung. Tujuan dari penelitian ini untuk mengetahui apakah ada perbedaan pengetahuan guru PAUD sebelum dan setelah diberikan pelatihan pembelajaran ABK. Peserta penelitian ini adalah guru yang berasal dari Kota Parepare. Jumlah peserta yang terlibat dalam penelitian ini 35 orang guru PAUD. Penelitian ini merupakan penelitian pra-experimental design dengan jenis one-grup pretest-posttest design. Instrument penelitian ini menggunakan instrument tes dan angket respon guru. Data penelitian didapatkan melalui pemberian tes yang diberikan sebelum dan setelah pelaksanaan treatment. Hasil penelitian ini adalah pengetahuan guru PAUD dalam pembelajaran ABK mengalami peningkatan secara signifikan. Hal ini menunjukkan bahwa pelatihan pembelajaran ABK berdampak positif untuk meningkatkan pengetahuan guru PAUD.Kata Kunci: Guru PAUD, Pembelajaran Anak Berkebutuhan Khusus